2017
DOI: 10.21037/mhealth.2017.01.01
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile phone use among female entertainment workers in Cambodia: an observation study

Abstract: Background: Text or voice messages containing health behavior change content may be an inexpensive, discreet, sustainable and scalable way to reach populations at high risk for HIV. In Cambodia, one of the important high-risk populations is female entertainment workers (FEWs). This ethnographic study aims to explore typical phone use, examining patterns and behaviors that may influence the design of future mHealth interventions. Methods:The study consisted of one 8-hour non-participant observation session for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In the Asian-Pacific countries, the number of mobile social media users was set to reach one billion by the fourth quarter of 2015; and in Cambodia, increasing 108% from the previous year [ 45 ]. According to our recent observation study, FEWs have both smart and basic mobile phones, use them daily to text and engage in social media, and have expressed interest in receiving health information through their phones [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Asian-Pacific countries, the number of mobile social media users was set to reach one billion by the fourth quarter of 2015; and in Cambodia, increasing 108% from the previous year [ 45 ]. According to our recent observation study, FEWs have both smart and basic mobile phones, use them daily to text and engage in social media, and have expressed interest in receiving health information through their phones [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still other authors noted this dichotomy within their reported results with some participants expressing significant privacy concerns and others stating it to not be an issue [146,147]. While some users expressed such concerns related to collection of highly sensitive-data, such as that related to behavioral health, reproductive health, or HIV status [135,[148][149][150][151], other users who provided such data still reported little unease related to their privacy [139,142,[152][153][154]].…”
Section: Dynamic User Attitudes Toward Privacymentioning
confidence: 98%
“…User concern with privacy of personal data collected by mobile health apps is widely variable. In some studies, data privacy and security was cited as of primary concern or importance [74,134,138], while in others, users expressed very little concern [125,[139][140][141][142][143][144][145]. Still other authors noted this dichotomy within their reported results with some participants expressing significant privacy concerns and others stating it to not be an issue [146,147].…”
Section: Dynamic User Attitudes Toward Privacymentioning
confidence: 99%
“…Given, FSW’s increasing use of technologies for health information seeking [90, 91], refining and tailoring O2O models is of urgent priority to address substantial gaps in optimal HIV prevention uptake [92, 93]. …”
Section: The Way Forwardmentioning
confidence: 99%